Non-communicable diseases control in China and Japan - Fei Wu; Hiroto Narimatsu; Xiaoqiang Li; Sho Nakamura; Ri Sho; Genming Zhao; Yoshinori Nakata; Wanghong Xu (BMC, 2017)
Abstract China and Japan share numerous similarities other than their geographical proximity. Facing the great challenges of non-communicable diseases (NCDs), China and Japan have developed different preventive strategies and systems. While Japan has made great progress in primary prevention of NCDs through strong legislation, the 'Specific Health Check and Guidance System' and a unique licensed health professional system, China is attempting to catch up by changing its strategies in NCDs control. In this manuscript, we compared disease burden of NCDs, health care systems and preventive strategies against NCDs between China and Japan. In this light, we summarized the points that the two countries can learn from each other, and proposed recommendations for the two countries in NCDs control.